2002
DOI: 10.1163/156855402760194692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber surface treatments on the fiber–matrix interaction in banana fiber reinforced polyester composites

Abstract: Effect of fiber surface treatments on the fiber-matrix interaction in banana fiber reinforced polyester compositesCitation for published version (APA): Pothan, L. A., George, J., & Thomas, S. (2002). Effect of fiber surface treatments on the fiber-matrix interaction in banana fiber reinforced polyester composites. Composite interfaces, 9(4), 335-353. Document status and date:Published: 01/01/2002 Document Version:Publisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 25 publications
3
46
0
3
Order By: Relevance
“…However, this study found that filters became more fragile as percentages of Si-69 increased, thus 2% of Si-69 was used instead of 3%. As the tensile strength increases, the toughness decreases (Pothan et al, 2002) and this may account for the brittleness in our study.…”
Section: Binder Effect On Photocatalysismentioning
confidence: 52%
“…However, this study found that filters became more fragile as percentages of Si-69 increased, thus 2% of Si-69 was used instead of 3%. As the tensile strength increases, the toughness decreases (Pothan et al, 2002) and this may account for the brittleness in our study.…”
Section: Binder Effect On Photocatalysismentioning
confidence: 52%
“…Estas melhorias nas propriedades são consequência do aumento de área superficial de contado da fibra com a matriz devido à desfibrilação promovida cisalhamento ocorrido durante o processo de extrusão e favorecida pelo tratamento alcalino. De acordo com Pothan et al [35] , além da desfibrilação, o tratamento alcalino promove a diminuiu sua acidez da superfície da fibra, devido a presença de grupos OH, contribuindo para o aumento da interação polar-polar entre a matriz e a fibra.…”
Section: -Efeito Do Tratamento Alcalino De Fibras De Curauá Sobre As unclassified
“…Después de los tratamientos la superficie de las fibras es mas lisa, lo que incrementó su homogeneidad y la hidrofobicidad de su superficie. Estos cambios afectan positivamente la interacción inter-facial fibra-matriz y mejoran las propiedades de los MC tal como también fue observado en otros estudios (Pothan, et al, 2002) (Shah, et al, 2013). Efectos similares fueron observados, cuando se tratan FSP con silano a diferentes porcentajes.…”
Section: Prueba De Tensiónunclassified